A Model-Based Estimation of Annual Long-Term Care Costs in Germany Following Post-Operative Cognitive Dysfunction (POCD) in Elderly Patients - Simon A. Weber; Malte Pietzsch; Claudia Spies; Fatima Yürek; Daniel Hadzidiakos; Friedrich Borchers; Florian Lammers-Lietz; Sophie K. Piper; Jochen Kruppa; Georg Winterer (Journal of Public Health International, 2021)
Acute post-operative delirium (POD) and long-term post-operative cognitive dysfunction (POCD) are frequent and associated with increased mortality, dependency on care giving and institutionalization rates. The POCD-related cost burden on the German long-term care insurance provides an indication for the savings potential from risk-adapted treatment schemes. Comprehensive estimates have not been assessed or published so far. A model-based cost-analysis was designed to estimate POCD-related costs in the long-term care insurance. Comprehensive analysis of inpatient operations and procedures (OPS-codes) served as the base for case number calculations, which were then used as input to the actual cost model. POCD-incidence rates were obtained from the BioCog study. Various sensitivity analyses were performed to assess uncertainty of the model results. Total POCD related annual costs in the German long-term care insurance account for approximately 1.6 billion EUR according to the base case of our analysis. Total annual costs for all POCD cases depend on surgery numbers, incidence rates, other assumptions, and uncertain input parameters. The financial burden to the long-term care insurance is substantial, even in a conservative scenario of the cost model. Variability of results stems from uncertain assumptions, POCD-incidence rates and from uncertain patient numbers who are undergoing surgery and are therefore at risk to develop POCD.
Keywords: Post-Operative Cognitive Dysfunction